Intention to shop online amongst MBA students: Applicability of the theory of reasoned action (TRA) - Ramayah, T.; Aafaqi, Bushra (2005)
Internet has changed the way business is conducted and one of the emerging uses of the Internet is for shopping.With an increasing affluent community the potential of Internet shopping cannot be ignored.The purpose of this paper is to test the applicability of the TRA (Fishbein & Ajzen, 1975; Ajzen & Fishbein, 1980) in predicting the intention to shop online among a group of Masters of Business Administration students of a public institution of higher learning.A structured questionnaire was used to elicit information from MBA students using a convenience sampling techniques.A total of 102 responses were received.The findings indicate that the TRA is a valid model in the prediction on the intention to shop online.Attitude (β = 0.575, p< 0.01) and subjective norm (β = 0.213, p< 0.01) were found to be positively related to intention with attitude being the more influential predictor. Subjective norm also positively influences (β = 0.374, p< 0.01) the attitude to shop online.